GAMBARAN PENGETAHUAN, SIKAP DAN TINDAKAN IBU POST PARTUM DALAM PERAWATAN TALI PUSAT BAYI DI KOTA KUPANG - ursula nona (CHMK MIDWIFERY SCIENTIFIC JOURNAL, 2020)
Caring umbilical cord is a measure to care baby’s umbilical cord after or before it is amputated. This research aims to know description of mothers’ knowledge, attitude, and action after bear a child in caring babies’ umbilical cord in Kupang. This research is a descriptive research which done at 4 local government clinics. They are local government clinic of Sikumana, Bakunase, Pasir Panjang, and Alak. Sampling technique used in this research is Consecutive Sampling technique with total responder is 60. Research instrument used is questioner and check list sheets. Result of research shows that mothers’ knowledge in caring umbilical cord is at enough level (48, 3%); mothers’ attitude in caring babies’ umbilical cord is at enough level ( 41,7%); as well as mothers’ action in caring babies’ umbilical cord is at enough level (50,0%). Therefore local government clinic should give effort to increase mothers’ knowledge, attitude and action in caring babies’ umbilical cord in order to prevent infection.